What Every Teacher should Know to Reduce Examination Stress Some Intervention Strategies - Singh, Veer Pal (JOURNAL OF INDIAN EDUCATION, 2013)
This paper is intended to explore the intervention strategies which can be carried out at school for reducing the examination stress among school students. The gravity of this issue of examination stress reduction has been addressed in the National Curriculum Framework – 2005 which has suggested various reforms in the examination system like enhancement of time for answering the question paper, examination of shorter duration, making class X public examination optional, reporting of students’ performance in terms of grades, flexibility in opting the subjects of choice for study and examinations, on-demand examination, introduction of Continuous and Comprehensive Evaluation (CCE) etc. Consequently, Boards of School Education have initiated various reforms to address this issue. But the role of school and teachers’ can not be ignored as the child spends about six to eight hours every day in school. It is the highest duration next to the time spent at home by the child. Therefore, the interventional strategies like creating congenial physical environment at school, cognitive and academic assistance, social-emotional support and stress busting mechanisms at school are suggested. Each strategy is discussed in the light of teachers’ and students’ roles in a number of situations which may arise in a child’s school life.